1984
DOI: 10.1159/000172942
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Statistical Investigation of the Occurrence of ‘Tubule-Like Cells’ in the Renal Corpuscle of the Mouse Kidney Induced by Sex Hormones

Abstract: In this report the authors describe the structural and ultrastructural characteristics of some cells constituting the parietal layer of Bowman’s capsule of the mouse kidney, which are very similar to the epithelial cells of the proximal convoluted tubule (tubule-like cells). These elements are noted in mature and immature mice of both sexes, but their fine morphology and statistical incidence seem related to the sex and the age of the mice, as revealed by the different responsiveness of the same animals to sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
9
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
4
9
0
Order By: Relevance
“…It has been reported that androgen promotes the apperance of cuboidal cells in the parietal layer of the glomerular capsule of the mouse kidney [2]. Therefore, we examined the effects of castration and sex hormone treatment, and confirmed the same effect by testosterone, although no effect was brought about by estradiol.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…It has been reported that androgen promotes the apperance of cuboidal cells in the parietal layer of the glomerular capsule of the mouse kidney [2]. Therefore, we examined the effects of castration and sex hormone treatment, and confirmed the same effect by testosterone, although no effect was brought about by estradiol.…”
Section: Discussionmentioning
confidence: 54%
“…Since the first report by Selye [12] in 1939, a large number of studies have been reported on the cuboidal epithelium in the parietal layer of the glomerular capsule of adult male mice [1,2,[4][5][6][7][8][9]. In the present study, we examined the appearance of this epithelium and expressed it as percentages of renal corpuscles with cuboidal cells in the parietal layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The CPL of the glomerular capsule, which has a similar function to the proximal tubular epithelium [4], is a feature of the renal corpuscles in adult male mice in many strains [1,11,15]. Such a CPL is also found in the small percentage of renal corpuscles of female mice [2,15], and it was reported that the percentage of the renal corpuscles with a CPL is higher during proestrus and estrus [2].…”
mentioning
confidence: 97%
“…In this study, the renal corpuscles with a CPL area under 50% showed similar changes to the previous report [2], although the renal corpuscles with a CPL area over 50% were unchanged by the estrous cycle. It has been reported that testosterone and dehydroepitestosterone treatments promote the appearance of CPL in the renal corpuscles [1,15], although the effects of 17β-estradiol treatments have been denied in these reports. Both testosterone and dehydroepitestosterone are the precursors of estrogen, and it might be presumed that these hormones and/or other ovarian androgens, e.g.…”
mentioning
confidence: 99%